Estimating the causal relationship between electricity consumption and industrial output: ARDL bounds and Toda-Yamamoto approaches for ten late industrialized countries. Issue 6 (June 2019) - Sankaran, A.; Kumar, Sanjay; K, Arjun; Das, Mousumi
Abstract: This research investigates the effects of electricity consumption (major independent variable), per capita income, real exchange rate, import and export on manufacturing output by using yearly time series data for the period of 1980–2016 with regard to 10 late industrialized nations. The ARDL bound testing approach, the way to deal with cointegration is applied to estimate the long-run connection between the variables. While, error correction method (ECM) is used to find the short-run dynamics. To test the causality among the variables, Toda-Yamamoto test is performed. The results demonstrate the existence of short-run and long-run relationship among the variables and Toda-Yamamoto causality results support the existence of growth, conservation, feedback and neutrality hypotheses for different nations. The difference in the results can be attributed to structural and macroeconomic parameters. In general, this research brings out a fresh lead of knowledge for late industrialized nations to strengthen their economic development through proficient utilization of energy consumption.